Conformational and electronic study of N-phenylalkyl-3,4-dichloromaleimides: Ab initio and DFT study - Zamora, Miguel Angel (2003)
A conformational and electronic study on N-phenylalkyl-3,4-dichloromaleimides, a new series of antifungal compounds, was carried out. In this study ab initio [RHF/3-21G and RHF/6-31G(d)] and density functional theory (B3LYP/6-31G(d)) calculations were performed. The effect of solvent (water) was taken into account by performing calculations with the isodensity polarizable continuum model method. The electronic study of the compounds was carried out using molecular electrostatic potentials. The presence of two symmetrical aromatic systems reduces notably the conformational possibilities of these maleimides. The results permit the recognition of the minimal structural requirements for the production of the antifungal response; a 3,4-dichloroimido ring and a benzene ring appear to be indispensable. Also, theoretical calculations suggest that the optimum interatomic distance between these moieties is about 3.5-5.0 Å.